Penyuluhan Tentang Demam Berdarah Dan Pencegahannya - Yuliana; Machrumnizar; Suriyani; Arleen Devita (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Dengue hemorhagic fever (DHF) is an infection caused by dengue virus. Dengue is a virus that is transmitted from Aedes Spp mosquito, the fastest growing mosquito in the world and has transmitted dengue virus. The prevalence of DHF until July 2020 has reached 71.633 in Indonesia, and 4.227 cases only in DKI Jakarta province. We usually don’t find new case on July, but this year we still find new cases on July. This should increase our vigilance, especially at this time when there is a pandemic of COVID-19 cases. The purpose of this activity is to increase public knowledge about dengue fever so that they can prevent dengue fever in their area. This activity is carried out through seminar using the zoom application because conditions in the field do not allow offline activities to be held. The activity will be held on Saturday, April 23, 2022. The results obtained through this PKM activity is an increase in the level of participants' knowledge about DHF as evidenced by an increase in post-test scores after attending the seminar. The conclusion of this PKM activity went well because of the support from all related parties from institutions, solid teams, and partners who actively participated. The shortage of this PKM activity is that the activities are carried out online because the conditions are still not conducive to do an offline activity. The advice we can give is to carry out PKM activities again with the same partner with different health topics according to the conditions that exist in the partners.